Comparison of Apical Microleakage of Canals Filled with Resilon/Epiphany, Thermafil/Adseal and Gutta Percha/Adseal - Mozayeni, Mohammad Ali; Dianat, Omid; Azadnia, Sina; Alam, Mostafa; Momenkhani, Sodayfeh (Journal of Dental School, 2013)
Objective: Root canal obturation is an important step in endodontic therapy aiming at achieving a complete three-dimensional seal of the canal and preventing microleakage, reentry or growth of microorganisms in the root canal system. Several techniques and materials are available for root canal filling. Achieving an apical seal is among the most important characteristics of filling materials. This study aimed to compare apical microleakage of three different canal obturation techniques of Thermafil/Adseal, lateral condensation with gutta percha/Adseal and lateral condensation with Resilon/Epiphany using dye penetration method. Methods: This experimental study was conducted on 51 anterior single-rooted human teeth. The teeth were sterilized, the crowns were cut and canals were prepared using the crown-down technique. The teeth were randomly divided into 3 groups of 15 each for the three techniques and 6 teeth were assigned to positive and negative control groups. The first group roots were filled with Thermafil/Adseal, the second group received gutta percha/Adseal with lateral condensation technique and group 3 teeth roots were filled with Resilon/Epiphany using lateral condensation technique. Microleakage was measured using dye penetration technique. Data were statistically analyzed using ANOVA. Results: Gutta percha/Adseal had the lowest (6.46(4.27) mm) and Resilon/Epiphany had the highest (13.47(3.03) mm) apical microleakage. Thermafil/Adseal showed higher mean apical microleakage than gutta percha/Adseal (8.43(4.49) mm). Statistical analysis revealed significant differences in apical microleakage among the three groups (p=0.0001). Conclusion: The results showed that gutta percha/Adseal had the lowest and Resilon/Epiphany had the highest mean apical microleakage. The microleakage of Thermafil/Adseal ranked second.